ダイ 25 ジ エットウ タイ カイヨウ セイブツ ケンキュウ カツドウ ホウコク 1984/85 BIOMASS ケイカク ダイ 3 ネンジ ノ カツドウ ヲ チュウシン ト シテ - 川口, 弘一; カワグチ, コウイチ; 松田, 治; マツダ, オサム; 石川, 慎吾; イシカワ, シンゴ; Kawaguchi, Kouichi; Matsuda, Osamu; Ishikawa, Shingo (1987)
P(論文) 第25次日本南極地域観測隊越冬隊生物グループは, BIOMASS計画の第3年次として(1)海水中有機物(とくに炭素, 窒素とリン)の動態(2)定着氷下における魚類, オキアミ類の生態の2点に重点を置いて研究を実施した。野外観測と室内での分解実験, 飼育実験を併用して, 野外での炭素とリンの循環およびナンキョクオキアミとショウワギスの生態に関し新知見を得た。このほかBIOMASS計画3ヵ年を通じて毎月一回定常的に行われた定点における各種海洋観測, 動・植物プランクトンの定量採集, およびアデリーペンギンとウェッデルアザラシのセンサスと生態調査を併せて行った。またBIOMASS関連研究のほかに陸上鮮類群調査および従来継続されてきた湖沼水, 土壌細菌, 土壌藻類のモニタリングを定法により実施した。 The biological research group of the 25th Japanese Antarctic Research Expedition (JARE-25,1984/85) conducted the studies on (1) the dynamics of organic carbon, nitrogen and phosphorus cycles, and (2) the ecology of krill and fish under the coastal fast ice in Lutzow-Holm Bay, which represent an activity in the last year of the three-year BIOMASS programme planned in the Japanese Antarctic Station, Syowa. Based on both field and laboratory experiments, new knowledges were obtained on the decomposition of particulate matter with special reference to the fate of carbon, nitrogen and phosphorus, and the ecology of notothenid fish, Trematomus bernachii and Antarctic krill, Euphausia superba under the fast ice. Oceanographical observations, including T, S, NH_3-N, NO_2-N, NO_3-N, PO_4-P, SiO_3-Si, D.O., PH and Chl. a measurements, and standard samplings of phytoplankton and zooplankton were made monthly at the 3 stations which had been fixed during the 3 year programme. Population censuses of Adelie penguin and Weddell seal were also included as a part of the programme. Besides the BIOMASS-oriented research, moss flora survey and monitoring of lake waters, soil bacteria and algae were also carried out at several definite lakes or points as a routine research programme. departmental bulletin paper